IMPLEMENTASI KEBIJAKAN PENANGGULANGAN STUNTING DI KECAMATAN BREBES - Chairunnisa, Amaliah; Larasati Setianingsih, Endang; Lituhayu, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The stunting control policy is a policy from the government to create a superior generation, because the stunting problem is an important issue that must be solved because it has an impact on the quality of human resources in the future. This study aims to analyze the implementation of stunting control policies in Brebes District, by analyzing the inhibiting factors in the implementation of stunting control policies in Brebes District. This policy is based on Regent Regulation Number 50 of 2019 concerning Stunting Control. In the stunting control policy, there is the First Thousand Days of Life (HPK) program, the Healthy Living Community Movement (Germas), family independence and nutrition education. This research method uses descriptive qualitative using the policy implementation theory put forward by Van Meter and Van Horn from the aspect; policy standards and objectives, resources, inter- organization relations, characteristics of implementing agents, dispositions and conditions of the social, economic and political environment. This study uses primary data through interviews with informants and secondary data obtained through other sources. The results of the study show that policy implementers have carried out their duties well, ranging from nutrition counseling to intervention programs. However, there is still a significant challenge, namely low public awareness of the importance of stunting prevention, even though campaigns and socialization have been carried out. In addition, another obstacle faced is that the legal framework used still refers to laws that have not been updated, so it does not fully support the change in needs on the ground.